THEOLOGICAL EDUCATION OF THE LAITY - L. Fernandes, Anthony (Asian Horizons, 2018)
This article studies briefly the history, the importance, and the sources for the theological education of the laity. In the first place, delving especially into the work, Theologia of Edward Farley, we recall the three stages that ‘theology’ and ‘theological education’ has passed through. In the patristic and early medieval period, theology was a salvifically oriented mystical knowledge of God that was available to all Christians through grace. In this sense, all Christians were ‘theologians’ and had access to theological education. In the second period theology becomes more of a discipline and a science, available in universities, creating thereby a certain separation between those who “studied theology” (clergy) and those who did not (laity). From theology as knowledge of God, it devolves into knowledge about God. In the third stage, with the establishment of the seminaries, theological education is restricted to the clergy. Farley recovers the original meaning of theology, showing that theological education is meant for all Christians. The article then recalls the new thinking in the 19th and 20th centuries when theologians rediscovered the original meaning of the Church as the People of God and the concept of the common priesthood of all Christians. This teaching was reflected in the various documents of the Vatican II. If the laity have to grow in holiness and influence the world, their theological education is a must. The article then enumerates some concrete means available for the theological education for the laity.